2019
DOI: 10.1093/jmammal/gyz166
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of movements with body mass in a small opossum: evidence for an optimal body size in mammals

Abstract: Movement by mammals generally increases with body size, described by a positive exponent scaling with either home range area or day range distances. Below ca. 100 g, however, interspecific comparisons suggest a negative scaling, increasing movement with decreasing body size. Such a pattern is expected from the rising costs of thermoregulation below ca. 100 g, implying that it should also be observed in intraspecific comparisons. We tested this hypothesis by investigating the scaling exponent of daily home rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…We believe that sex can be related to individual body mass (sexual size dimorphism, Lindenfors et al 2007), and that both sex and body mass should explain part of variability observed in movement, as found in many mammals' species (e.g. Vieira et al 2019 andLidgard et al 2020).…”
Section: Structural Equation Modelingmentioning
confidence: 93%
“…We believe that sex can be related to individual body mass (sexual size dimorphism, Lindenfors et al 2007), and that both sex and body mass should explain part of variability observed in movement, as found in many mammals' species (e.g. Vieira et al 2019 andLidgard et al 2020).…”
Section: Structural Equation Modelingmentioning
confidence: 93%
“…In this Special Feature, many of Bob's Ph.D. students offer contributions illustrating two themes that have consistently run through his research: 1) small mammals, and 2) New World mammals, as well as the breadth of his knowledge and interests (Beasley and Maher 2019;Esselstyn et al 2019;McCain 2019;Soley-Guardia et al 2019;Vieira et al 2019;Woodman and Wilken 2019;York et al 2019). Although Bob's graduate students were and remain fiercely independent in their research (a quality he probably sought out, and certainly encouraged), this collection of manuscripts encapsulates his own interests remarkably well.…”
Section: Papers Of This Special Featurementioning
confidence: 95%
“…For example, home-range sizes typically scale with body mass (Noonan et al, 2019), as larger species generally require more resources and therefore larger areas to access these resources (Tucker et al, 2014). Homerange size can also be affected by various other factors, such as habitat type and quality (Pop et al, 2018;Vieira et al, 2019), climatic conditions (Fieberg & B€ orger, 2012;Gosselink et al, 2003), sex (Phillips et al, 1998;Vanak & Gompper, 2010), and individual differences (Noonan et al, 2020). Thus, patterns of home-range use represent a cognitive map of spatially and temporally varying resource requirements and constraints as perceived by the animal (Powell & Mitchell, 2012).…”
Section: Introductionmentioning
confidence: 99%